Dynamic linkages between price indices and inflation in Malaysia - Rafiqa Murdipi,; Siong, Hook Law (Penerbit Universiti Kebangsaan Malaysia, 2016)
This study examines the dynamic linkages among consumer price, producer price, industrial production and import price indices in Malaysia by using monthly data from 2005 to 2013. The empirical results based on Johansen multivariate cointegration test reveal that there is a long-run relationship among these indices. The long-run estimations indicate that industrial production and import prices are statistically significant determinants of consumer price index, which indicates that Malaysian inflation is due to demand-pull and international transmission, or imported inflation in the long-run. However, the higher producer price is associated with higher inflation or costpush inflation in the short-run.